Pengaruh Pembuatan Konten Video Terhadap Penjualan Di B21 Digital Printing - Dzaka Zaki Syahansyah; Hesty Prima Rini (Pakis Journal Institute, 2024)
The purpose of this research is to provide an explanation of the marketing approach used by B21 Digital Printing. This approach provides an opportunity to utilize the MetaAds movie promotion platform to increase sales. By utilizing MetaAds as a marketing tool, B21 Digital Printing was able to achieve higher customer acquisition rates. This was achieved by consistently expanding audience reach through the utilization of enlightening and challenging video content. The information displayed here shows that the utilization of MetaAds as a digital platform for advertising produces high-quality results, which in turn validates the effectiveness of the video advertising strategy that B21 Digital Printing uses to facilitate the acquisition process of its portfolio of business opportunities.